2011
DOI: 10.1016/j.ultras.2010.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of the attenuation coefficient using a clinical array transducer for the detection of cervical ripening in human pregnancy

Abstract: Premature delivery is the leading cause of infant mortality in the United States. Currently, premature delivery cannot be prevented and new treatments are difficult to develop due to the inability to diagnose symptoms prior to uterine contractions. Cervical ripening is a long period that precedes the active phase of uterine contractions and cervical dilation. The changes in the microstructure of the cervix during cervical ripening suggest that the ultrasonic attenuation should decrease. The objective of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 23 publications
1
54
0
Order By: Relevance
“…We can rewrite equation The size of the ROI was varied in both the axial and lateral direction. Our previous studies have shown that approximately 15 pulse lengths in the axial direction and 15 pulse lengths in the axial direction and 15 echoes in the lateral direction gave a standard deviation on the order of 25% in the attenuation estimates for simulations, phantom experiments, and in the rat cervix when using the spectral log difference algorithm, while the spectral difference algorithm had a standard deviation of less than 13% for the same ROI size [9,37,39].The pulse length was calculated by taking the auto correlation coefficient of time samples from RF echo lines of the phantom data. Samples with absolute correlation coefficient greater than 0.2 were considered correlated and determined the time pulse length.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…We can rewrite equation The size of the ROI was varied in both the axial and lateral direction. Our previous studies have shown that approximately 15 pulse lengths in the axial direction and 15 pulse lengths in the axial direction and 15 echoes in the lateral direction gave a standard deviation on the order of 25% in the attenuation estimates for simulations, phantom experiments, and in the rat cervix when using the spectral log difference algorithm, while the spectral difference algorithm had a standard deviation of less than 13% for the same ROI size [9,37,39].The pulse length was calculated by taking the auto correlation coefficient of time samples from RF echo lines of the phantom data. Samples with absolute correlation coefficient greater than 0.2 were considered correlated and determined the time pulse length.…”
Section: Methodsmentioning
confidence: 97%
“…Our previous studies had shown that approximately 15 pulse lengths in the axial direction and 15 echoes in the lateral direction gave a standard deviation on the order of 25% in the attenuation estimates when the tissue was homogeneous. Therefore, we varied our region sizes about these values for our study [11,37,39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The attenuation coefficient slope (ACS), combined with other statistical parameters and tissue properties (i.e., image texture, backscatter coefficients), has been used to diagnose diffuse liver diseases [1,2] and characterize breast tissues [3]. Attenuation coefficients have been proposed as potential tools for predicting cervical ripening in rats [4] and humans [5]. The possibility to differentiate between Graves' and Hashimoto's thyroid disease based on ACS estimates has been explored [6].…”
Section: Introductionmentioning
confidence: 99%
“…[6] In addition, ultrasonic attenuation has been shown to decrease with increasing gestational age. [7] However, the effects of the angle of interrogation of the beam, position within the cervix, parity, and ripening of the nonpregnant cervix have not been reported.…”
Section: Introductionmentioning
confidence: 99%